74 Seaside Avenue - Macomber, Debbie (Don Mills, Ont. : Mira, 2007)
While catching up on all the Cedar Grove gossip, Teri Polgar senses that something is amiss with her new husband Bobby, a famous chess champion, when he begins acting strangely.
Keywords: Beauty operators; Chess players; Washington (State); Love stories